Deaths during tuberculosis treatment among paediatric patients in a large tertiary hospital in Nigeria - Adamu, Aishatu L. (PLoS One, 2017)
BACKGROUND: Despite availability of effective cure, tuberculosis (TB) remains a leading cause of death in children. In many high-burden countries, childhood TB is underdiagnosed and underreported, and care is often accessed too late, resulting in adverse treatment outcomes. In this study, we examined the time to death and its associated factors among a cohort of children that commenced TB treatment in a large treatment centre in northern Nigeria. METHODS: This is a retrospective cohort study of children that started TB treatment between 2010 and 2014. We determined mortality rates per 100 person-months of treatment, as well as across treatment and calendar periods. We used Cox proportional hazards regression to determine adjusted hazard ratios (aHR) for factors associated with mortality. RESULTS: Among 299 children with a median age 4 years and HIV prevalence of 33.4%; 85 (28.4%) died after 1,383 months of follow-up. Overall mortality rate was 6.1 per 100 person-months. Deaths occurred early during treatment and declined from 42.4 per 100 person-months in the 1(st) week of treatment to 2.2 per 100 person-months after at the 3(rd) month of treatment. Mortality was highest between October to December period (9.1 per 100 pm) and lowest between July and September (2.8 per 100 pm). Risk factors for mortality included previous TB treatment (aHR 2.04:95%CI;1.09–3.84); HIV infection (aHR 1.66:95%CI;1.02–2.71), having either extra-pulmonary disease (aHR 2.21:95%CI;1.26–3.89) or both pulmonary and extrapulmonary disease (aHR 3.03:95%CI;1.70–5.40). CONCLUSIONS: Mortality was high and occurred early during treatment in this cohort, likely indicative of poor access to prompt TB diagnosis and treatment. A redoubling of efforts at improving universal health coverage are required to achieve the End TB Strategy target of zero deaths from TB.